Study on Cell Adhesion Detection onto Biodegradable Electrospun PCL Scaffolds (Journal of Fiber Bioengineering and Informatics, 2012)
The polycaprolactone (PCL) known for its slow biodegradability shows potential applications in the fieldof skin scaffold production. In the current study PCL mats with micro scaled structure were producedvia electrospinning and treated with NaOH solution for enhanced cell adhesion. The scaffolds wereevaluated as an efficient stem cell growing material by human skin keratinocytes and fibroblasts culture.The cell viability assay (CellTiter-Blue) of the as spun scaffolds was compared with previously preparedPU electrospun scaffolds, fibrin scaffolds and amniotic membrane scaffold. Significant difference in celladhesion was evident between the natural and synthetic scaffolds. As far as the electrospun scaffoldswere concerned the significance between, as well as for the NaOH treated, samples was less evident. Therepetition of different donor cells fluorescence within the same scaffold material was also present.
Keywords: NaOH Treatment; Keratinocytes; Fibroblasts; Cell Culture